PENGARUH LOVE OF MONEY, ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN KECERDASAN EMOSIONAL PADA KINERJA PEGAWAI UNIVERSITAS UDAYANA - Martini, Putu; Mimba, Ni Putu Sri Harta; Rasmini, Ni Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.01.TAHUN 2017, 2016)
This study aims to examine the effect of love of money, organizational citizenship behavior and emotional intelligence on the performance of Udayana University employees. The study was conducted by using quantitative data with the source of primary data gathered through a questionnaire that had been tested for validity and reliability. The population was state employees of Udayana University with the research sample of 259 people who were determined based on Slovin formula. The analysis technique used is by using multiple linear regression analysis. The results of this study show that the love of money has no effect on the performance of the employees while the organizational citizenship behavior and emotional intelligence have a positive effect on employees’ performance. In addition, emotional intelligence has a more dominant effect on the performance compared with the love of money and organizational citizenship behavior.
Keywords: love of money, organizational citizenship behavior, emotional intelligence, performance of employees